prove the following:
Answers
Answered by
31
Given:
__________________________
Prove That:
__________________________
Solution:
L.H.S,
Multiply, both numerator and denominator with 1 - cos θ
Using, (a + b) (a - b) = a² - b²
Using, 1 - cos² θ = sin² θ
Multiply, both numerator and denominator with 1 + cos θ
Using, (a + b) (a - b) = a² - b²
Using, 1 - cos² θ = sin² θ
Hence, Proved
____________________________
Extra Shots:
ZzyetozWolFF:
niceeeeeee!
Similar questions
Math,
3 months ago
Math,
3 months ago
English,
6 months ago
Hindi,
6 months ago
CBSE BOARD X,
1 year ago